1980
DOI: 10.3177/jnsv.26.343
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic alterations in the endogenous formation of 6 keto-prostaglandin F1.ALPHA., thromboxane B2 and prostaglandin E2 in the brain-stem of stroke-resistant spontaneously hypertensive rats.

Abstract: SummaryEndogenous biosynthetic capacities for prostaglandin (PG)E2, thromboxane (TX)B2 (a stable degradation product of TXA2) and 6 keto-PGF1a (a stable degradation product of PGI2) in the brain stem fractions of stroke-resistant spontaneously hypertensive rats (SHRSR) and control Wistar-Kyoto rats (WKR) were determined with novel methods and presented in an original report. In comparison with WKR, it is characteristically found that TXB2 synthesis is increased in excess of threefold in the pons-medulla oblong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1981
1981
1983
1983

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This might be reflected on a relatively smaller amount of PGEz formation in differentiated adhesive cells. It was already confirmed that a neuroblastoma clone N 18, whose differentiated revertants formed more PGEz than TXB2, made conspicuous neurite extensions when 0.2-0.5 mM of N6, Oz'-dibutyryl 3', 5'-monophosphate or 20-50 pg/ml of PGE2 coexisted with 2 x lo3 -2 x lo4 cells from day 4 to day 6 (during the logarithmic phase) [14].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This might be reflected on a relatively smaller amount of PGEz formation in differentiated adhesive cells. It was already confirmed that a neuroblastoma clone N 18, whose differentiated revertants formed more PGEz than TXB2, made conspicuous neurite extensions when 0.2-0.5 mM of N6, Oz'-dibutyryl 3', 5'-monophosphate or 20-50 pg/ml of PGE2 coexisted with 2 x lo3 -2 x lo4 cells from day 4 to day 6 (during the logarithmic phase) [14].…”
Section: Discussionmentioning
confidence: 75%
“…This might be reflected on a relatively smaller amount of PGEz formation in differentiated adhesive cells. It was already confirmed that a neuroblastoma clone N 18, whose differentiated revertants formed more PGEz than TXB2, made conspicuous neurite extensions when 0.2-0.5 mM of N6, Oz'-dibutyryl 3', 5'-monophosphate or 20-50 pg/ml of PGE2 coexisted with 2 x lo3 -2 x lo4 cells from day 4 to day 6 (during the logarithmic phase) [14]. tion from multipotential cells in our cultures, but attachment per se is not necessarily the critical condition, as Mintz's group [ l l ] already pointed out, since the effect may be mediated by a deposit of some other cellular product(s) such as glycoprotein or collagen [21].…”
Section: Discussionmentioning
confidence: 85%
“…An endogenous l O formation of the order PGD2 > PGF2, > PGE2 is found when rat hypothalamic or median eminence tissue in incubated in vitro (Wolfe, 1982). Furthermore, thromboxane B2 (TxB2) and 6-keto-PGF1, is formed in the hypothalamus indicating synthesis of PGI2 and the presence of the thromboxane pathway in this brain region (Ohtsu & Matsuzawa, 1980). Taken together, these reports indicate that PGD2, PGF,A, PGE2 and PGI2 are formed in the brain areas which are implicated in the physiological regulation of gastric secretion, viz.…”
Section: Discussionmentioning
confidence: 97%